Do investors value the FDA orphan drug designation? - Kathleen L. Miller (Orphanet Journal of Rare Diseases, 2017)
Abstract Background The Orphan Drug Act is an important piece of legislation that uses financial incentives to encourage the development of drugs that treat rare diseases. This analysis studies the effects of a portion of the Orphan Drug Act, the orphan drug designation. Specifically, it studies the value that investors place on the orphan drug designation, by investigating how investors react to companies’ announcing that their product has received the designation. Results The results, on average, show that the stock price of a company increases by 3.36% after the announcement of the designation, increasing the value of the company. The results are more pronounced for oncology drugs, and drugs being developed by the smallest companies. Conclusion The orphan designation appears to be successful at generating positive value for companies, as seen by the positive and significant average increases in stock price.